A Review of Extraction and Analytical Methods for the Determination of Tartrazine (E 102) in Foodstuffs. (4th July 2017) - Rovina, Kobun; Siddiquee, Shafiquzzaman; Shaarani, Sharifudin Md
ABSTRACT: Tartrazine is an azo food dye, which is orange-colored and water soluble. It is usually used in foods, pharmaceuticals, cosmetics, and textiles. Tartrazine has the potential to cause an adverse health effect on humans, such as hyperactivity in children, allergy, and asthma. Joint FAO/WHO Expert Committee on Food Additive and EU Scientific Committee for Food have standardized the acceptable daily intake for tartrazine that is 7.5 mg kg −1 body weight. Many researchers have detected the presence of tartrazine for monitoring the quality and safety of food products. In this review paper, we highlighted various tartrazine detection and extraction methods. Some of the analytical methods are available such as high-performance liquid chromatography, electrochemical sensor, thin-layer chromatography, spectrophotometry, capillary electrophoresis, and liquid chromatography-tandem mass spectrometry. Also, we discuss following extraction steps: liquid–liquid extraction, solid-phase extraction, membrane filtration, cloud point extraction, and other extraction method. In addition, a brief overview is presented explaining the synthesis process and metabolism of tartrazine and the maximum permitted level in different countries. This review paper will give an insight into different extraction and analytical methods for the determination of tartrazine in healthy foods, which will attract the attention of public toward food safety and quality, and also the interest of food industry and government bodies.